Understanding the Pathophysiology of Female Infertility: A Systematic Review with Special Reference to Anovulation - Desai, Gautami; Kumbar, Jyoti; Yadav, Rajesh (Journal of Neonatal Surgery, 2025)
Female infertility is a multifactorial condition influenced by various physiological, hormonal, and environmental factors, with Anovulation being one of the primary causes. Anovulation results from disruptions in the hypothalamic-pituitary-ovarian (HPO) axis, leading to hormonal imbalances such as elevated luteinizing hormone (LH), decreased follicle-stimulating hormone (FSH), hyperprolactinemia, insulin resistance, and thyroid dysfunction. Conditions like polycystic ovarian syndrome (PCOS), primary ovarian insufficiency (POI), and hypothalamic dysfunction further contribute to ovulatory dysfunction. From an Ayurvedic perspective, Anovulation is associated with an imbalance of Vata and Kapha Dosha, affecting Artava Dhatu (reproductive tissue) and Rajovaha Srotas (reproductive channels). Poor dietary habits, sedentary lifestyles, chronic stress, and metabolic disorders contribute to Agnimandya (digestive fire impairment) and Ama (toxins), further aggravating ovarian dysfunction. Ayurvedic interventions, including Panchakarma, Rasayana therapies, herbal formulations, and dietary modifications, aim to restore hormonal balance and improve ovulatory function. This systematic review explores the pathophysiology of female infertility with a special focus on Anovulation, integrating modern biomedical insights with Ayurvedic principles. Understanding these underlying mechanisms is crucial for developing targeted therapeutic approaches to enhance fertility outcomes.